Existence of diffusive processes with the given local characteristics - Osypchuk, M.M. (Carpathian Mathematical Publications, 2009)
The results which concern to existence of diffusive processes with the given local characteristics (vector of drift, operator of diffusion) are considered in the article. The processes are examined in separable Hilbert space. Some properties of such processes (equivalence of measures, connection with stochastic differential equations) are also considered.